First-Year Trajectories of Medical Cannabis Use Among Adults Taking Opioids for Chronic Pain: An Observational Cohort Study. Issue 12 (19th August 2021) - Ross, Jonathan; Slawek, Deepika E; Zhang, Chenshu; Starrels, Joanna L; Levin, Frances R; Sohler, Nancy L; Minami, Haruka; Arnsten, Julia H; Cunningham, Chinazo O
Abstract: Objective: To describe first-year trajectories of medical cannabis use and identify characteristics associated with patterns of use in a cohort of adults using opioids for chronic pain. Design: Latent class trajectory analysis of a prospective cohort study using data on the 14-day frequency of medical cannabis use. Setting: A large academic medical center and four medical cannabis dispensaries in the New York City metropolitan area. Subjects: Adults with chronic pain using opioids and newly certified for medical cannabis in New York between 2018 and 2020. Methods: Using latent class trajectory analysis, we identified clusters of participants based on the 14-day frequency of medical cannabis use. We used logistic regression to determine factors associated with cluster membership, including sociodemographic characteristics, pain, substance use, and mental health symptoms. Results: Among 99 participants, the mean age was 53 years; 62% were women, and 52% were White. We identified three clusters of medical cannabis use: infrequent use (n = 30, mean use = 1.5 days/14-day period), occasional use (n = 28, mean = 5.7 days/14-day period), and frequent use (n = 41, mean = 12.1 days/14-day period). Within clusters, use patterns did not vary significantly over 52 weeks. Differences were observed in two sociodemographic variables: Frequent (vs infrequent) use was associated with non-Hispanic White race/ethnicity (adjusted odds ratio 4.54, 95% confidence interval 1.49–14.29), while occasional (vs infrequent) use was associated with employment (adjusted odds ratio 13.84, 95% confidence interval 1.21–158.74). Conclusions: Three clusters of medical cannabis use patterns emerged and were stable over time. Results suggest that structural factors related to race/ethnicity and employment may be major drivers of medical cannabis use, even among adults certified for its use.